Pengaruh Etnosentrisme Konsumen pada Preferensi Konsumen Studi: Perbandingan Preferensi Konsumen WNI Keturunan India pada Produk Bercorak India Dibanding Produk Bercorak Non-India - Reza Febriani; V. Rachmadi Parmono (Faculty of Economics and Business, Universitas Stikubank, 2021)
This study discusses the extent of consumer preferences of Indonesian citizens of Indian descent in Indian-patterned products compared to non-Indian-patterned products. This study aims to determine the preference of Indonesian consumers of Indian descent in Indian-patterned products compared to non-Indian patterns. This research uses quantitative methods. The method used to obtain primary data by disseminating it directly to Indonesian citizens of Indian descent. The collected d ata were analyzed by analysis of mean, crosstab , and regression analysis. Based on the data analysis that has been carried out, the results of the study obtained several findings as follows. Based on regression analysis, ethnocentrism affects consumer preferences. Based on Analysis Chi Square, ethnocentrism has no relation to respondents' age, gender, income, education, or occupation